Customer’s satisfaction towards Uber service among university students in Kota Samarahan, Sarawak / Terrance Manja Janting and Josephson Louis Nako - Janting, Terrance Manja; Nako, Josephson Louis (UNIVERSITI TEKNOLOGI MARA CAWANGAN SARAWAK, 2018)
This chapter consist often sub topics. The first sub topic is introduction followed by the second sub topic background of study. The third sub topic is the problem statement. The fourth sub topic is the research question which followed by the fifth sub topic which is research objective, these two sub topics must be aligned because it connected with each other and must remained consistent. Next, the sixth sub topic which is the significance of the research followed by the seventh sub topic which is hypothesis which is making assumptions. The eight sub topic is the scope of study where the research took place and then followed by the definition of terms which is the ninth sub topic is divided into two components which is conceptual and operational. The last but not least of the sub topic is the chapter summary which summarized the whole chapter.